Gender Gaps in Primary School Achievement: A Decomposition into Endowments and Returns to IQ and Non-cognitive Factors - Bart H.H. Golsteyn; Trudie Schils (Institute for the Study of Labor (IZA), 2014)
In elementary school, girls typically outperform boys in languages and boys typically outperform girls in math. The determinants of these differences have remained largely unexplored. Using rich data from Dutch elementary schools, we decompose the differences in achievement into gender differences in endowments and returns to IQ and non-cognitive factors. This descriptive analysis is a thought experiment in which we show the consequences for school performance if girls and boys would have similar resources and take similar advantage of these resources. Our findings indicate that gender differences in resources with respect to social and instrumental skills and need for achievement can explain part of the differences in performance. Boys seem to be better equipped with these resources. Additionally, boys and girls employ their skills differently. Girls take more advantage of their IQ than boys. Yet, the largest part of this parameter effect is left unexplained by IQ and non-cognitive factors.
Keywords: I21; I24; 330; decomposition; achievement; education; gender; personality